ANALISIS DOMAIN KOMPETENSI KONDISI FISIK MENGGUNAKAN TES KEBUGARAN PELAJAR NUSANTARA (TKPN) PADA SISWA SMP NEGERI 14 MATARAM - Ranika Anjani; Dadang Warta Chanra WK.; Kurnia Taufik (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
This study aimed to analyze the physical fitness domain of students at SMP Negeri 14 Mataram using the Tes Kebugaran Pelajar Nusantara (TKPN). A quantitative descriptive design was used with 44 students consisting of 22 boys and 22 girls. The analysis focused on four TKPN performance components available in the dataset, namely the PACER test, squat thrust, sit and reach, and sit up. Data were analyzed using descriptive statistics and percentage distributions based on fitness categories. The findings showed that boys consistently demonstrated a better fitness profile across all test components. In the PACER test, 50.0% of boys were classified as good and 9.1% as very good, while 81.82% of girls were classified as poor. Similar patterns were found in squat thrust, sit and reach, and sit up, where the proportion of girls in the poor category ranged from 72.73% to 81.82%. These findings indicate a clear descriptive gap in physical fitness profiles between boys and girls. TKPN can serve as a practical school-based tool for monitoring student fitness and for designing more targeted physical education interventions.